Treponema denticola increases MMP‐2 expression and activation in the periodontium via reversible DNA and histone modifications. (8th January 2018) - Ateia, Islam M.; Sutthiboonyapan, Pimchanok; Kamarajan, Pachiyappan; Jin, Taocong; Godovikova, Valentina; Kapila, Yvonne L.; Fenno, J. Christopher
Abstract: Host‐derived matrix metalloproteinases (MMPs) and bacterial proteases mediate destruction of extracellular matrices and supporting alveolar bone in periodontitis. The Treponema denticola dentilisin protease induces MMP‐2 expression and activation in periodontal ligament (PDL) cells, and dentilisin‐mediated activation of pro‐MMP‐2 is required for cellular fibronectin degradation. Here, we report that T .  denticola regulates MMP‐2 expression through epigenetic modifications in the periodontium. PDL cells were treated with epigenetic enzyme inhibitors before or after T .  denticola challenge. Fibronectin fragmentation, MMP‐2 expression, and activation were assessed by immunoblot, zymography, and qRT‐PCR, respectively. Chromatin modification enzyme expression in T .  denticola‐ challenged PDL cells and periodontal tissues were evaluated using gene arrays. Several classes of epigenetic enzymes showed significant alterations in transcription in diseased tissue and T .  denticola ‐challenged PDL cells. T .  denticola ‐mediated MMP‐2 expression and activation were significantly reduced in PDL cells treated with inhibitors of aurora kinases and histone deacetylases. In contrast, DNA methyltransferase inhibitors had little effect, and inhibitors of histone acetyltransferases, methyltransferases, and demethylases exacerbated T .  denticola ‐mediated MMP‐2 expression and activation. Chronic epigenetic changes in periodontal tissues mediated by T .  denticola or other oral microbes may contribute to the limited success of conventional treatment of chronic periodontitis and may be amenable to therapeutic reversal.